Analisis Kemampuan Penalaran Matematis Siswa MTs. NW Senyiur terhadap Kemampuan Pemahaman Konsep Matematika - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The aims of this study are: 1) to describe the ability to understand concepts through students' mathematical reasoning on the Cube and Block material; and 2) to determine the relationship between the mathematical reasoning abilities of MTs. students NW Senyiur with the ability to understand the concept of Cube and Block material. This research is a qualitative descriptive study conducted on 25 MTs. students NW Senyiur on the material of cubes and blocks. Data on students' mathematical reasoning abilities were collected through Mathematical Reasoning Tests (non-routine questions), while students' conceptual understanding abilities were collected through Concept Understanding Tests (routine questions). The two tests given each consist of 2 questions. In addition, interviews were conducted to collect more complete information from the sample that had been studied. Research data were analyzed by Pearson Product-Moment Correlation Test. The results of this study indicate that: 1) the average grade IX MTs. students NW Senyiur has good reasoning ability and conceptual understanding; and 2) there is no relationship between mathematical reasoning ability and concept understanding ability of grade IX MTs. students NW Senyiur on the material of cubes and blocks. The magnitude of the significant value that exceeds the provisions and the standard significance value is > 0.05, then there is no significant correlation (H0 is accepted). Thus, it can be concluded that, in this study, there is no relationship between mathematical reasoning abilities and students' conceptual understanding abilities.